Description of a multidisciplinary model of care in a French cohort of adult patients with tuberous sclerosis complex. Issue 1 (14th May 2020) - Pfirmann, Pierre; Aupy, Jerome; Jambon, Eva; Idier, Laetitia; Prezelin-Reydit, Mathilde; Fermis, Marine; Devillard, Raphael; Grenier, Nicolas; Combe, Christian; Rigothier, Claire
Abstract : Background: Tuberous sclerosis complex (TSC) is a rare autosomal dominant genetic disorder. Due to the various manifestations of TSC and their potential complications, a multidisciplinary care approach is recommended by consensus guidelines. Objectives: Our study aimed to give a complete description of our TSC adult cohort and to evaluate the multidisciplinary and interdisciplinary management model. Methods: Data on each adult patient diagnosed with TSC, including disease manifestations, interventions and outcomes, were collected at baseline and updated annually. A multidisciplinary TSC approach with all the recommended explorations was carried out annually. Results: 90 patients were enrolled in Centre Hospitalier Universitaire de Bordeaux, between January 2000 and September 2018. Median age of patients at inclusion was 37 years (range, 27–47) and 20 years old at diagnosis of TSC. Regarding the occurrence of TSC manifestations, 97% of the patients had cutaneous lesions, 89% had neurological manifestations, 83% had renal manifestations and 100% had dental lesions with pits. More than half the patients had sclerotic bone lesions (68%), TSC-associated neuropsychiatric disorders (64%) and lymphangioleiomyomatosis (59%). A TSC multidisciplinary approach was developed including a global follow-up and an evaluation of TSC targeting organs, according to the recommendations. A satisfaction survey revealed global and entire satisfaction of patients with TSC. Conclusion: We obtained an accurate description of a cohort of adult patients with TSC. Our multidisciplinary approach model allowed us to provide optimal management of patients with TSC with a high level of patient satisfaction.